The features and burden of headaches within a chiropractic clinical population: A cross-sectional analysis. (January 2020) - Moore, Craig; Leaver, Andrew; Sibbritt, David; Adams, Jon
Highlights: This paper examines the healthcare use of chiropractors by those with headache disorders. Those who consult chiropractors with headache often have features of common recurrent headaches, including migraine and tension headache. Increased headache burden is common amongst those who consult chiropractors for headache management. Abstract: Objectives: The aim of this study is to a) investigate the headache features and level of headache severity, chronicity, and disability found within a chiropractic patient population and b) to ascertain if patient satisfaction with headache management by chiropractors is associated with headache group or reason for consulting a chiropractor. Design and setting: Consecutive adult patients with a chief complaint of headache participated in an online cross-sectional survey (n = 224). Recruitment was via a randomly selected sample of Australian chiropractors (n = 70). Headache features were assessed using International Classification of Headache Disorders criteria and level of headache disability measured using the Headache Impact Test instrument. Results: One in four participants (n = 57; 25.4%) experienced chronic headaches and 42.0% (n = 88) experienced severe headache pain. In terms of headache features, 20.5% (n = 46) and 16.5% (n = 37) of participants had discrete features of migraine and tension-type headache, respectively, while 33.0% (n = 74) had features of more than one headache type. 'Severe' levels of headache impact were most often reported in those with features of mixed headache (n = 47; 65.3%) and migraine (n = 29; 61.7%). Patients who were satisfied or very satisfied with headache management by a chiropractor were those who were seeking help with headache-related stress or to be more in control of their headaches. Conclusion: Many with headache who consult chiropractors have features of recurrent headaches and experience increased levels of headache disability. These findings may be important to other headache-related healthcare providers and policymakers in their endeavours to provide coordinated, safe and effective care for those with headaches.